Filsafat Ilmu Manajemen Pendidikan: Hakikat Kebenaran Ilmiah - Gusnita, Fitria; Annisa, Mella; Triana, Mamy; Ardimen, Ardimen; Zulfadwal, Zulfadwal (FAKULTAS TARBIYAH UNIVERSITAS QOMARUDDIN GRESIK - JAWA TIMUR, 2025)
Basically, humans have a natural tendency to think; the purpose of this process is to produce knowledge and truth. Knowledge helps answer questions and problems faced by humans. Thus, science is needed to answer the challenges faced by humans. Thus, the author will examine the nature of truth, the criteria for scientific truth: types and characteristics, Furthermore, the method for finding scientific truth in the field of Islamic education management. This paper closes by concluding the problem. The method used is qualitative and uses a library research approach. This research was conducted by collecting a number of data and information from the results of the literature, and then presenting new findings. The results of the study indicate that truth is an important aspect in the search for accurate and valid knowledge. The concept of truth is often identified as the correspondence between a statement or belief with objective reality, but other philosophical approaches also recognize truth through coherence, consensus, and pragmatism. Scientific truth has characteristics that are closely related to the scientific method. Scientific knowledge is tentative and can be revised as human understanding develops. The criteria for scientific truth often involve aspects such as logical rationality, empirical content, and can be applied pragmatically